INDEKS LITERASI KESEHATAN KELUARGA PENDERITA ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS BETUNGAN KOTA BENGKULU - Leni Delta; Afriyanto Afriyanto; Henni Febriawati; Fahreza Kurnia Sari (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
Health literacy is a person's understanding of the application of health in everyday life, both in prevention, treatment, treatment, and making appropriate and fast decisions. Bengkulu Province is one of the five provinces with the highest prevalence of ARI nationally and is one of the causes of most deaths in children under five. This type of research is quantitative descriptive and data collection techniques using interview guidelines using questionnaires. The results of the study found that children and toddlers who were most infected with ARI were children aged 16 months to 5 years, with a total of 50 respondents. The literacy index of families with ARI sufferers in children under five in the Betungan of Bengkulu Health Center is still inadequate, and this is related to the limited activities of health promotion activities. Keywords: Health Literacy, ARI, Toddler